(untitled) (Security Dialogues, 2025)
National security is a segment that is considered from the perspective of an integral part of the theory of regional security complex. The focus of this paper is to determine the relevance of the state national interests, with special reference to giving appropriate proposals in the part of better management of them in the future and its more adequate complementarity during the renewal of strategies. The necessity of rebuilding the national interests is necessary in order to monitor the fight against modern threats. The need to specify long-term national interests is of vital importance for every modern state, so our state needs to build a solid foundation for the analogous functioning of all segments of the state system by specifically defining strategic national interests based on the existing ones. Analogous to what was written, certain theoretical proposals were given that would be useful in terms of the survival of national interests as the core of a state and a guide for further strategic challenges.